Minority language abandonment in Welsh-medium educated L2 male adolescents: classroom, not chatroom. Issue 2 (3rd May 2016) - Price, Abigail Ruth; Tamburelli, Marco
ABSTRACT: The education system has played a crucial role in Welsh language maintenance, with Welsh-medium education providing a central locus of language transmission. However, language transmission through education is not without pitfalls. This paper discusses the impact of top-down minority language transmission and the growing issue of formal domain dependency in Wales. We present results of 4 focus groups, undertaken with 19 male adolescent L2 speakers of Welsh. The key findings indicate that top-down formal-domain transmission has amplified the view of Welsh as a language limited to formal, 'high' domains, thus inhibiting language application among male adolescents. The inherent association of Welsh with formality as well as tradition and patriotism has led to cultural disengagement among the target group.